Potential Analysis of Bitcoin Cryptocurrency as a Future Investment Asset: A Systematic Literature Review - Jesika, Silvia; Widya Pratiwi; Deni Handani; Hamirul (Open Access Indonesia Journal of Social Sciences, 2023)
Despite this promising potential, it is important to remember that investing in Bitcoin also involves risk. The price of Bitcoin is very volatile, and its value can change dramatically in a short amount of time. In addition, regulations regarding cryptocurrencies are still unclear in many countries, and regulatory changes could affect the price and adoption of Bitcoin. Security is also an important factor, as Bitcoin can be vulnerable to cyberattacks and theft. This study aimed to conduct studies related to the potential of bitcoin cryptocurrency as an asset for future investment as well as the potential risks that exist in this asset. Literature search efforts are carried out by searching on search engines using certain keywords. Articles that match the inclusion criteria are reviewed in depth. Bitcoin's potential as a future investment alternative is highly dependent on factors such as value growth, institutional adoption, and developments in blockchain technology. Nonetheless, it is important to be aware of the risks associated with investing in cryptocurrencies and to carry out in-depth research and consulting before making any investment decisions.